THE PORTRAYAL OF JAKE SULLY PERSONALITY TRAITS AND HIS SOCIAL INTERACTION IN THE AVATAR MOVIE - Afina Murtiningrum; Eva Alfiona Fitricianingtyas; Destary Praptawati; Riana Permatasari (Universitas Duta Bangsa Surakarta, 2024)
Every person is created with a unique character that distinguishes one from another in terms of personality traits that defines the way he interacts with the society. Jake Sully, as the main character in the Avatar movie, portrays this relationship between personality traits and social interactions. This research used the Avatar (2009) movie by James Cameron as the object of the research and applied the personality traits theory from Costa and McCrae and the social interaction theory from Tischler. The research methodology used was descriptive qualitative. Two types of data were primary and secondary data. Primary data were taken from the movie Avatar. Meanwhile, secondary data were taken from e-books, e-journals, and articles about personality traits and social interaction. Watching the movie, reading the movies script, identifying data, classifying data, and reducing data were done in collecting the data. The result finds that the personality traits in Jake Sully are extraversion, agreeableness, conscientiousness, and openness to experience. Moreover, the social interactions experienced by Jake Sully are non-verbal behavioral, exchange, cooperation, and conflict. Finally, it can be concluded that personality traits influences the social interaction of a person.